THE INFLUENCE OF ORGANIZATIONAL COMMITMENT AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE - Fitria Damayanti; Didit Darmawan (Jurnal Manajemen Bisnis dan Terapan, 2025)
An important part of business operations is good employee management. Building responsibility within the organization, making activities enjoyable, and improving employee capabilities are all ways to achieve this. If a company wants to succeed and be successful, employee satisfaction is essential. Job satisfaction is felt by employees when the results have their own satisfaction for their goals, influenced by intrinsic factors, namely within themselves and extrinsic factors, namely the existence of motivation by external parties so that they feel that their work results have been appreciated in the form of rewards, career development, incentives, or other gifts. The positive relationship between the two shows that the higher the commitment and satisfaction, the higher the performance produced. Strong commitment to the organization and employee job satisfaction are two internal factors that can affect employee performance. This qualitative research analyzes literature that includes articles and academic publications relevant to the research topic. The research findings reveal that loyalty to the organization and operational satisfaction affect employee performance; it is necessary to pay more attention to commitment as well as employee responsibility and job satisfaction so that each can help the company succeed by increasing strong commitment to the organization, creating satisfaction at work, and producing optimal employee performance.